EVALUATION OF THE ADEQUACY OF SCIENTIFIC SECTOR FINANCING DIRECTIONS TO THE SCIENTIFIC-TECHNICAL DEVELOPMENT PRIORITIES PROCLAIMED BY THE STATE - N. A. Shakina (Russian Journal of Economics and Law, 2013)
Objective: To reveal the discrepancies of the actual state financing of scientific sectors and the proclaimed priorities of the national scientific-technical development. Methods: Historical and logical methods are used for the study of evlution of the problem stating and continuity of its solution; abstract-logical for theoretical summarizing and forming conclusions; economical-statistical for analyzing the modern condition of the state financing of scientific sectors in Ukraine; analysisand synthesis methods for revealing the volume and directions of financing of national science; comparative analysis for comparing the actual directions of science financing with the proclaimed national priorities of the scientific-technical development of the country. Results: Discrepancy with the proclaimed priorities of the national scientific-technical development of the country is revealed basing on the data of state statistics, as well as the absence of the clearly stated priorities of the national economic development. Scientific novelty: Discrepancy of the legally stated actual priorities of the innovative economical development of the country is grounded, decelerating the further improving of the national development strategy. Practical value: The carried out analysis and research results are a basis for further deeper study of the directions of the country’s innovative development and elaborating recommendations for improving the system of conceptual provisions and measures of state strategy of innovations development in Ukraine, as well as the conternt of normative-legal acts on the issues of scientific-technical development of the economy.